Layer-specific optogenetic activation of pyramidal neurons causes beta–gamma entrainment of neonatal networks - Sebastian H Bitzenhofer; Joachim Ahlbeck; Amy Wolff; J. Simon Wiegert; Christine E. Gee; Thomas G. Oertner; Ileana L. Hanganu-Opatz (Nature Communications, 2017)
Oscillations in cortical activity during development are important for functional maturation. Here, the authors use optogenetics in neonatal mice to determine a causal role for pyramidal cell firing in different prelimbic cortex layers in generating beta–gamma range activity.